Monitoring Phosphoinositide Fluxes and Effectors During Leukocyte Chemotaxis and Phagocytosis - Montaño-Rendón, Fernando; Grinstein, Sergio; Walpole, Glenn F. W. (Frontiers in Cell and Developmental Biology, 2021)
The dynamic re-organization of cellular membranes in response to extracellular stimuli is fundamental to the cell physiology of myeloid and lymphoid cells of the immune system. In addition to maintaining cellular homeostatic functions, remodelling of the plasmalemma and endomembranes endow leukocytes with the potential to relay extracellular signals across their biological membranes to promote rolling adhesion and diapedesis, migration into the tissue parenchyma, and to ingest foreign particles and effete cells. Phosphoinositides, signalling lipids that control the interface of biological membranes with the external environment, are pivotal to this wealth of functions. Here, we highlight the complex metabolic transitions that occur to phosphoinositides during several stages of the leukocyte lifecycle, namely diapedesis, migration, and phagocytosis. We describe classical and recently developed tools that have aided our understanding of these complex lipids. Finally, major downstream effectors of inositides are highlighted including the cytoskeleton, emphasizing the importance of these rare lipids in immunity and disease.